Core needle biopsy for the assessment of unilateral male breast lesions. Issue 4 (April 2017) - Bicchierai, G.; Nori, J.; Livi, L.; De Benedetto, D.; Vanzi, E.; Boeri, C.; Bianchi, S.; Becherini, C.; Meattini, I.
Abstract: The importance of preoperative histological diagnosis in the assessment of breast lesions in women is widely established, but in men with breast lesions histological diagnosis is obtained in a limited number of cases. The aim of this study was to report our single-center experience in a large series of 131 CNB performed for suspicious male breast lesions. Our data confirmed that CNB is an effective method in distinguishing between benign and neoplastic lesions in the male breast, thus validating the few published data. CNB should be a routine part of the unilateral male breast swelling diagnostic assessment, being precious tool for the clinicians for surgery planning or avoidance.